Mity i kontrmity, przyczynek do dyskusji o polskiej tożsamości historycznej - Connelly, John (Pamięć i Sprawiedliwość, 2005)
How should Poland deal with Western ignorance about its history? The misconceptions are so huge, especially about World War II, that many Poles react with understandable defensiveness. But uncritical views of the Polish past – which stress only the positive – will convince no-one, and are in any case unsound history. There is perhaps no more bothersome and unpleasant topic at the moment for historically minded Poles than supposed “Polish collaboration” with the Nazis. But if one approaches the matter dispassionately, one sees that Poland has nothing to fear from probing considerations of this issue. There are of course controversial issues that need to be explored indepth: the actions of the construction battalions (Baudienst), the Institut für deutsche Ostarbeit, the local Polish police (policja granatowa), the exact practices of signing Poles onto the Volkslisten. But when the dust clears, Poland remains the country in Europe that did the least to support the Nazi war effort. Its oppositional stance is explained, however, not through ideologically based determination of Nazi Germany to destroy Poland. In fact, the Nazis had wanted Poland as an ally. But Poland refused. This refusal lay not in some superior moral quality that happened to animate the Poles of an earlier period, but rather in an absolute determination of Poles to protect national sovereignty. Polish nationalism – good, bad, and neutral – functioned to rule out collaboration in the minds of Polish leaders and Polish citizens. In this case historical analysis can help defuse an emotionally charged issue. There is much that was heroic and inspiring in Polish history. But once one rejects a protective attitude toward the Polish past – one that confuses history for myth – one can also make better use of that past. It becomes something not to feel proud of – after all we have inherited it, not created it – but something to measure up to, a recognition that we stand on others shoulders and that the circumstances we inherit are not of our own making. Heroic deeds of the past thus inspire the humility of respect rather than the arrogance of fear. A similar argument might be made about Polish Stalinism: for very specific historic reasons Poles cooperated in constructing of the new Soviet-type society far less than other subject peoples in East and Central Europe. But that would be the subject for a new essay.